Cost analysis of chronic heart failure management in Malaysia: A multi-centred retrospective study - Ong, Siew Chin; Low, Joo Zheng; Yew, Wing Yee; Yen, Chia How; Abdul Kader, Muhamad Ali S. K.; Liew, Houng Bang; Abdul Ghapar, Abdul Kahar (Frontiers in Cardiovascular Medicine, 2022)
Background Estimation of the economic burden of heart failure (HF) through a complete evaluation is essential for improved treatment planning in the future. This estimation also helps in reimbursement decisions for newer HF treatments. This study aims to estimate the cost of HF treatment in Malaysia from the Ministry of Health’s perspective. Materials and methods A prevalence-based, bottom-up cost analysis study was conducted in three tertiary hospitals in Malaysia. Chronic HF patients who received treatment between 1 January 2016 and 31 December 2018 were included in the study. The direct cost of HF was estimated from the patients’ healthcare resource utilisation throughout a one-year follow-up period extracted from patients’ medical records. The total costs consisted of outpatient, hospitalisation, medications, laboratory tests and procedure costs, categorised according to ejection fraction (EF) and the New York Heart Association (NYHA) functional classification. Results A total of 329 patients were included in the study. The mean ± standard deviation of total cost per HF patient per-year (PPPY) was USD 1,971 ± USD 1,255, of which inpatient cost accounted for 74.7% of the total cost. Medication costs (42.0%) and procedure cost (40.8%) contributed to the largest proportion of outpatient and inpatient costs. HF patients with preserved EF had the highest mean total cost of PPPY, at USD 2,410 ± USD 1,226. The mean cost PPPY of NYHA class II was USD 2,044 ± USD 1,528, the highest among all the functional classes. Patients with underlying coronary artery disease had the highest mean total cost, at USD 2,438 ± USD 1,456, compared to other comorbidities. HF patients receiving angiotensin-receptor neprilysin-inhibitor (ARNi) had significantly higher total cost of HF PPPY in comparison to patients without ARNi consumption (USD 2,439 vs. USD 1,933, p < 0.001). Hospitalisation, percutaneous coronary intervention, coronary angiogram, and comorbidities were the cost predictors of HF. Conclusion Inpatient cost was the main driver of healthcare cost for HF. Efficient strategies for preventing HF-related hospitalisation and improving HF management may potentially reduce the healthcare cost for HF treatment in Malaysia.